Hypoxic Burden and T90% as Predictive Indicators of Cardiovascular Risk and Myocardial Ischemia in Patients with Obstructive Sleep Apnea - Zeng W; Wu S; Liu Z; Yuan L; Chen B; Rong Y (Nature and Science of Sleep)
Wenmei Zeng,1,* Sulong Wu,2,* Zhuofan Liu,1 Long Yuan,1 Bilin Chen,1 Yan Rong1 1Department of Pulmonary and Critical Care Medicine, Shenzhen Qian Hai She Kou Free Trade Zone Hospital, Shenzhen, 518067, People’s Republic of China; 2Department of Emergency Intensive Care Medicine, Shenzhen Qian Hai She Kou Free Trade Zone Hospital, Shenzhen, 518067, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Rong, Department of Pulmonary and Critical Care Medicine, Shenzhen Qian Hai She Kou Free Trade Zone Hospital, No. 36, Gongye 7th Road, Nanshan District, Shenzhen, 518067, People’s Republic of China, Tel +86-13622230015, Email shanshuisahala@163.comPurpose: This study analyzed the role of hypoxic burden and the percentage of time with blood oxygen saturation below 90% (T90%) in assessing the myocardial ischemia and cardiovascular risk in obstructive sleep apnea (OSA) patients using portable sleep monitors.Patients and Methods: We conducted a prospective observational study of hospitalized OSA patients diagnosed by portable sleep monitors at a single tertiary center in Southern China from January 2022 to March 2024. Cardiovascular risk was assessed with the China-PAR model including anthropometric measurements and risk factors. Myocardial ischemia was evaluated via electrocardiogram. Factors including hypoxic burden severity categories, apnea-hypopnea index severity categories, respiratory event durations (apnea%, hypopnea%, and combined%), and oxygen desaturation metrics (T90%/T85%/T80%) were analyzed with binary logistic regression for 10-year atherosclerotic cardiovascular disease (ASCVD) risk and myocardial ischemia evaluation in OSA patients. The diagnostic value was analyzed with the receiver operating characteristic curve.Results: A total of 311 OSA patients were included, with a median age of 53 years, 75.6% of whom were male. Among them, 51.4% demonstrated electrocardiogram changes indicative of myocardial ischemia, and 55.3% had moderate-to-high 10-year ASCVD risk. Patients with moderate-to-high ASCVD risk had higher hypoxic burdens and T90%. Both the hypoxic burden and T90% showed significant predictive value for cardiovascular risk stratification. Clinically meaningful thresholds were established: 125.8%min/h for hypoxic burden and 3.05% for T90% in ASCVD risk prediction (area under the curve 0.747– 0.754), and 112.6%min/h and 4.20% for myocardial ischemia detection (area under the curve 0.741– 0.769).Conclusion: The hypoxic burden and T90% obtained from portable sleep monitors can be valuable indicators for assessing cardiovascular risk in OSA patients. Cardiovascular risk stratification increases patient and physician vigilance toward the detrimental effects of OSA and provides practical decision points for clinicians for further evaluation and treatment.Keywords: obstructive sleep apnea, hypoxic burden, myocardial ischemia, cardiovascular disease risk